2016
DOI: 10.3892/ijmm.2016.2609
|View full text |Cite
|
Sign up to set email alerts
|

Association of miR-34a, miR-130a, miR-150 and miR-155 polymorphisms with the risk of ischemic stroke

Abstract: Abstract. MicroRNAs (miRNAs or miRs) are small (19-23 nt) non-coding RNA molecules that are endogenous regulators of gene expression. Previous studies have found that some miRNAs are related to the progression of ischemia in the cerebral artery. Furthermore, a recent study found a significant association between miRNA single nucleotide polymorphisms (SNPs) and the risk of ischemic stroke. Therefore, it may be valuable to investigate associations between megakaryocyte formationrelated miRNA polymorphisms and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 44 publications
1
23
0
1
Order By: Relevance
“…While it is hard for external material to enter the seminiferous tubules because of the blood−testis barrier, we successfully used intratesticular injection to study the in vivo effect of miR‐130a in spermatogenesis. miR‐130a has been implicated in several diseases, including ischemic stroke (Choi et al, ) and cancer (Boll et al, ). It has been reported that miR‐130a directly target several components of the mitogen‐activated protein kinase and AR signaling pathways in prostate carcinoma (Boll et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is hard for external material to enter the seminiferous tubules because of the blood−testis barrier, we successfully used intratesticular injection to study the in vivo effect of miR‐130a in spermatogenesis. miR‐130a has been implicated in several diseases, including ischemic stroke (Choi et al, ) and cancer (Boll et al, ). It has been reported that miR‐130a directly target several components of the mitogen‐activated protein kinase and AR signaling pathways in prostate carcinoma (Boll et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…While it is hard for external material to enter the seminiferous tubules because of the blood−testis barrier, we successfully used intratesticular injection to study the in vivo effect of miR-130a in spermatogenesis. miR-130a has been implicated in several diseases, including ischemic stroke (Choi et al, 2016) and…”
Section: Discussionmentioning
confidence: 99%
“…pulmonary arterial hypertension [ 28 ] as well as in myocardial infarction [ 8 ]. In a recent study a polymorphism in the gene encoding for miR-150 was found to be associated with ischemic stroke [ 29 ]. Additionally, Cox proportional analysis indicated that the miR‑150GA genotype was associated with survival in patients with ischemic stroke [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Впоследствии было подтверждено повышение активности miR-146a в подострой стадии ИИ [49]. Установлено, что при ИИ miR-145 увеличивает объем оксидантного повреждения за счет подавления активности антиоксидантного фермента супероксиддисмутазы, которая играет важную роль в восстановлении ишемизированной клетки [50], а miR-146a подавляет экспрессию циклооксигеназы 2-го типа, которая продуцирует реактивный кислород, предупреждая развитие оксидантного стресса [51].…”
Section: микрорнк -регуляторы генной экспрессииunclassified